Treatment and risk factors of Internet use disorders. Issue 7 (10th February 2017) - Nakayama, Hideki; Mihara, Satoko; Higuchi, Susumu
Abstract : Recently, many young people have developed Internet use disorders (IUD) as a result of the proliferation of Internet‐enabled devices, leading to serious health and social problems worldwide. On occasion, medical and educational institutions, governments, and other groups have sought to take preventive action or treat IUD. In many cases, the preferred treatment for IUD is to set recommendations for appropriate Internet use. Reportedly, psychosocial therapies (including cognitive behavioral therapy, family therapy, and compound therapy) for IUD and pharmacotherapies (including antidepressant drugs and psychostimulants) for comorbid psychiatric or development disorders have been effective at reducing the degree and symptoms of IUD. In some countries, treatment camps have been developed for adolescents with IUD, and preventive education (including lectures and group discussions) has been provided for general adolescents. Such efforts have been effective at reducing the average degree of IUD severity. Some future IUD risk factors (e.g. being male, suffering from attention‐deficit hyperactivity disorder, and exhibiting deteriorating psychiatric symptoms) have begun to be identified. However, clinical studies, treatment, and preventive actions are insufficient for treating IUD and standard treatments and preventive systems have yet to be established. Educational and medical institutions, government, families, and others must take greater action and cooperate more effectively in order to treat or prevent IUD.